Measurement of the t(t)over-bar production cross section, the top quark mass, and the strong coupling constant using dilepton events in pp collisions at root s=13TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Ambrogi, Federico; Asilar, Ece; Md. Ali, Mohd. Adli (Springer New York LLC, 2019)
A measurement of the top quark–antiquark pair production cross section σtt in proton–proton collisions at a centre-of-mass energy of 13 TeV is presented. The data correspond to an integrated luminosity of 35.9 fb−1, recorded by the CMS experiment at the CERN LHC in 2016. Dilepton events (e±μ∓, μ+μ−, e+e−) are selected and the cross section is measured from a likelihood fit. For a top quark mass parameter in the simulation of mMC t = 172.5 GeV the fit yields a measured cross section σtt = 803 ± 2 (stat) ± 25 (syst) ± 20 (lumi) pb, in agreement with the expectation from the standard model calculation at next-to-next-toleading order. A simultaneous fit of the cross section and the top quark mass parameter in the powheg simulation is performed. The measured value of mMC t = 172.33 ± 0.14 (stat) +0.66 −0.72 (syst) GeV is in good agreement with previous measurements. The resulting cross section is used, together with the theoretical prediction, to determine the top quark mass and to extract a value of the strong coupling constant with different sets of parton distribution functions.